Konstruk Media Pembelajaran Baamboozle Pada SD Islam Sinar Cendekia - Winaningsih, Elis Tuti; Syarif, Fajar (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
This research explores the use of gamification in learning, especially the use of the Baamboozle platform. This is related to the role of PAI teachers in increasing students' learning motivation, especially in grade 5 at Sinar Scholar Islamic Elementary School. The aim of this research is to analyze teacher strategies in increasing student learning motivation in PAI classes. This research agrees with research entitled